Evaluating interventions on broiler chicken health using blood indices and graphical representation - Ghaleghafi, Abolfazl; Khorshidi, Kaveh Jafari; Jafari , Mohammad Ali Jafari (Acta Scientiarum. Animal Sciences, 2024)
Heat stress significantly affects the physiological and performance aspects of broiler chickens, leading to reduced growth, feed intake, and feed efficiency. This research investigates the impact of various dietary additives and supplements on blood serum components in heat-stressed Ross 308 broiler chickens. A completely randomized design with eight treatment groups, each with four replications and 12 birds per replication, was used. Significant differences were found in blood parameters such as glucose, total protein, albumin, uric acid, and AST, as well as in heterophil percentage, lymphocyte count, heterophil to lymphocyte ratio, and bronchitis antibody titers (p < 0.05). Dietary interventions also significantly altered the E. coli population in the cecum (p < 0.05). Diets enriched with coenzyme Q10 and vitamin C notably reduced E. coli populations under heat-stress. However, no significant differences were observed in tibia characteristics (p > 0.05). These results demonstrate the effectiveness of feed additives in mitigating heat stress effects in broiler chickens. We recommend incorporating vitamin C, coenzyme Q10, and Eubiotic supplements to enhance the well-being and performance of broiler chickens under heat stress conditions.